BAHAN AJAR MATEMATIKA REALISTIK MATERI KUBUS DAN BALOK UNTUK SEKOLAH MENENGAH PERTAMA - Elpriska, Elpriska; Hartoyo, Agung; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractLearning with realistic approach is one of the approach that relevant with prevailed curriculum. There is no teaching material that appropiate with local students characteristic. To fulfil it, the researcher did the research with the purpose to develop mathmatic teaching material in cube and beam subject. This research used ADDIE model, which has 5 steps namely analysis, design, development, implementation, and evaluation. The quality of teaching materials was developed by three aspects, which were validation which was obtained from the questionnaire’s module score of the material’s and media’s masters,  the effectiveness which was obtained from student’s score of post test, and pratical aspect based on the student’s result of their respon on the questionnaire. The result of this research showed three modul’s quality based on three aspects. From the validity, the researcher obtained the mean score was 3,9 which categorize as valid. From the effectiveness, it was obtained the class mean score was 76,77 and 73 % of their learning test result which categorized as good. Based on the practical aspect, the mean score was 4,44 which categorized as a very good. It conclude that the module which was used in this research was valid, effective, and practice. Keywords :  teaching material, cube and beam, RME